FAKTOR YANG BERHUBUNGAN PADA MOTIVASI PENGGUNA DAN IMPLEMENTASI REKAM MEDIS ELEKTRONIK DENGAN EFISIENSI PELAYANAN DI INSTALASI RAWAT JALAN RSUD KEBAYORAN LAMA - Kassiuw, Jean Francis Melanny; Hidayat, Budi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2024)
Electronic Medical Records (EMR) have emerged as an innovative solution in healthcare because EMR offers several advantages and provides a comprehensive solution to improve health information management in today’s digital era. This study applies the Technology Acceptance Model (TAM) as its theoretical foundation, aiming to evaluate the relationship between user perceptions of key factors influencing EMR implementation and service efficiency in the Kebayoran Lama Regional Hospital outpatient unit. The research design is non-experimental with a quantitative approach, utilizing numerical data analyzed through Structural Equation Modeling (SEM). The study collected data on user perceptions regarding EMR implementation and service efficiency through questionnaires filled out by 72 users as respondents, interviews with four stakeholders, and document reviews related to EMR implementation. Findings indicated significant relationships between the perceived usefulness of EMR and motivation, motivation and EMR implementation, and EMR implementation and service efficiency. These findings offer valuable insights for developing more effective EMR implementation strategies. Management can apply a fair reward and punishment mechanism, offering incentives for users consistently utilizing EMR and sanctions, such as reduced honoraria, for non-compliant users. Additionally, regular training tailored to individual needs, particularly for specialists, can improve comfort and proficiency in EMR use. Direct, responsive management support for user challenges can further boost motivation. Routine evaluations and active user involvement in feedback processes strengthen their sense of ownership toward the system, increasing motivation and commitment to EMR use.